Abortion for Fetal Genetic Abnormalities: Type of Abnormality and Gestational Age at Diagnosis - Tracy B. Grossman; Stephen T. Chasen (Thieme Medical Publishers, Inc., 2020)
Background Advances in genetic screening can identify patients at high risk for common genetic conditions early in pregnancy and can facilitate early diagnosis and early abortion. Less common abnormalities might only be diagnosed with invasive testing is performed after structural abnormalities are identified. Objective Our objective was to compare gestational age (GA) at diagnosis and abortion for genetic abnormalities identified based on screening with abnormalities that were not discovered after screening. Study Design All prenatal diagnostic procedures from 2012 to 2017 were reviewed, and singleton pregnancies terminated following diagnosis of genetic abnormalities were identified. Cases diagnosed as the result of screening tests were compared with remaining cases. Conditions were considered "screened for" if they can be suspected by cell-free DNA testing, biochemistry, carrier screening, or if the patient was a known carrier of a single-gene disorder. When abnormal karyotype, microarray, or Noonan's syndrome was associated with abnormal NT, these cases were considered "screened for." GA at abortion was the primary outcome. Fisher's exact test and Mann-Whitney's U test were used for statistical comparison. Results In this study, 268 cases were included. A total of 227 (85%) of abortions were performed for "screened for" disorders, with 210 (93%) of these for karyotype abnormalities, 5 (2%) for microarray abnormalities, and 12 (5%) for single-gene disorders. Forty-one (15%) of abortions were performed for conditions not included in screening, with 8 (19%) of those for karyotype abnormalities, 25 (61%) for microarray abnormalities, and 8 (19%) for single-gene disorders. Invasive testing and abortion occurred at earlier median GA for those with conditions that were screened for: 122/7 versus 155/7 weeks, p ≤0.001 and 135/7 versus 200/7 weeks; p ≤0.001. Conclusion Most abortions were for abnormalities that can be suspected early in pregnancy. As many structural abnormalities associated with rare conditions are not identifiable until the mid-trimester, prenatal diagnosis and abortion occurred significantly later. Physicians and patients should be aware of the limitations of genetic screening.